The Resection of a Thalamic Pilocytic Astrocytoma Through the Transchoroidal Fissure, Transcallosal Approach: 2-Dimensional Operative Video. Issue 5 (15th April 2021) - Kadri, Paulo A S; Ibn Essayed, Walid; Al-Mefty, Ossama
Abstract: Surgical resection is the primary treatment of pilocytic astrocytomas and total removal can be curative. However, these lesions occur in critical areas, such as the thalamus, being surrounded by critical life neurovascular structures, which imposes a surgical challenge. 1 -5 Exhaustive acquisition and meticulous interpretation of preoperative radiological exams; reliable surgical orientation based on profound microneurosurgical anatomic knowledge and judicious discernment of the neuroanatomic distortions on the surface and deep-seated structures inflicted by the neuropathological entity; embracing and comprehensive application of the vast scope of available intraoperative guidance imaging and neurophysiological monitoring; in alliance with the mastered carefully microsurgical technique supported by endoscopic visualization are the keystones to the pursed duet "cure with quality of life" in the treatment of these lesions. We present the case of a 17-yr-old young lady with a progressive motor deficit in her right hemibody for over 2 yr. Her radiological investigation demonstrated a left thalamic lesion displacing the projection fibers (corticospinal tract) within the internal capsule laterally. The patient consented to the surgical procedure. The surgical strategy, intraoperative findings, and microsurgical and endoscopic technique, as well as the postoperative radiological and clinical evaluation are presented. The patient gave her informed consent for the publication of the case.